(untitled) (Update Dental College Journal, 2014)
Children (below 13 yrs of age) are usually susceptible to cranio facial trauma because of their greater cranial mass to body ratio. When compared to adults, the pattern of fractures and frequency of associated injuries are similar but the overall incidence is much lower. Treatment is usually performed without delay and can be limited to observation or closed reduction in non-displaced or minimally displaced fractures. Operative management should involve minimal manipulation and may be modified by the stage of skeletal and dental development. Open reduction and rigid internal fixation is indicated for severely displaced fractures. When tooth buds within the mandible do not allow internal fixation with plates and screws, this can be achieved with a mandibular compression splint fixed to the teeth, to the mandible with circum-mandibular wire. Children require long-term follow-up to monitor potential growth abnormalities. A case of a 9-year-old boy with fractured body of mandible managed by closed reduction using occlusal acrylic splint and circum mandibular wiring is presented. DOI: http://dx.doi.org/10.3329/updcj.v3i2.18001 Update Dent. Coll. j: 2013; 3 (2): 55-60